Exploring the prospects and challenges of sustainable urban mobility: Potential and limits of cycling in Venice - Bircu, Cristina; Cavallaro, Federico; Pozzer, Gianfranco; Nocera, Silvio (Journal of Transport and Land Use, 2024)
The Covid-19 pandemic has affected the travel behavior of commuters, with soft modes emerging as reliable options for short-distance trips. This research focuses on evaluating the bike-friendliness of Venice, Italy, a unique city for its morphological and mobility characteristics. When considering daily commuting between the mainland and the historic city center in the lagoon, the bicycle is not an adopted solution. Yet, the recent construction of a bicycle and pedestrian path that runs alongside the main bridge between the mainland and historical city could alleviate the pressure on public transport and the use of cars, especially in peak hours. This contribution evaluates the potential for using bicycles to reach the historic center of Venice from the mainland, and the appropriateness of the infrastructural equipment. The quantitative analysis examines the current supply and demand in absolute values and in terms of modal share. Projecting the number of actual users under different scenarios until 2030, in accordance with the Venice Sustainable Urban Mobility Plan and other relevant plans, the inadequate provision of parking areas for bikes emerges as an unsolved issue. A revision of the mobility layout is thus required if bicycles are expected to be a competitive alternative solution.